ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA AUDITOR KANTOR AKUNTAN PUBLIK DI BALI - I Dewa Nyoman Wiratmaja; Ketut Alit Suardana (Jurnal Riset Akuntansi (JUARA), 2018)
This study aims to analyze the factors that affect the performance of auditors. Factors studied are organizational commitment, education level, amounts of fee and time budget pressure. The study population is all auditors in the Public Accounting Firm registered in Indonesian Institute of Certified Public Accountants of Bali in 2015. The sample is determined by non probabilty sampling method with purposive sampling technique. Selection of study respondents is determined by certain criteria. This study uses quantitative data sourced from primary data. Primary data is obtained from the spread of questionnaires on respondents and analyzed by using multiple linear regression analysis techniques. This research gives analysis result that organizational commitment have positive effect on auditor performance, education level have positive effect on auditor performance, fee has negative effect on auditor performance, and time pressure have positive effect on auditor performance.